An evaluation of an English coursebook “When English Rings The Bell” - Fransiskus Karsudianto (Journal of English Language Teaching Innovations and Materials (Jeltim), 2019)
This study aimed to evaluate an English course-book for eight graders entitled “When English Rings the Bell” published by the Ministry of Culture and Education of Indonesia in 2014. The study discussed what the teachers perceived as a good quality course-book and what recommendations they expected for the improvement of the course-book. The study was carried out in Bengkayang District. It employed a mixed-method with 15 English teachers as the research subjects.  It applied the convenience sampling method and collected data using a questionnaire designed based on Tomlinson’s course-book evaluation framework and analyzed by interpreting the subjects’ answers. The finding revealed that the teachers perceived the course-book positively with some recommendations for its improvement.